An Analysis of the Effect of Tiktok Affiliate Content Strategy on Affiliator Earnings Through Consumer Trust - Khusnul Indayani; Siti Mujanah; Achmad Yanu Alif Fianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
The rapid development of digital technology has created a new economic ecosystem through the integration of social media and marketing activities, particularly the TikTok Affiliate program. This program allows affiliates to earn performance-based income by influencing consumer purchasing decisions through creative and interactive content. This study aims to analyze TikTok affiliate content strategies in increasing income through consumer trust and behavior. The research employed a qualitative method with a literature review approach by analyzing various scientific sources related to affiliate marketing, consumer behavior, and social media algorithms. The results show that creative, relevant, and consistent content strategies significantly influence consumer trust and loyalty, which in turn increase affiliate income. Understanding the TikTok algorithm also plays an important role in determining the reach and effectiveness of promotional content. However, challenges such as limited promotional regulations, intense competition, and inequality between large and small affiliates remain obstacles. Overall, the TikTok Affiliate program has a positive impact on digital economic growth and the empowerment of Indonesia’s creative economy.